Supply Chain Management and Business Repute: A Case of Service Sector of Indonesia - Abdurohim, Dindin; Santoso, Adi (International Journal of Supply Chain Management, 2020)
Abstract- This research has assessed the empirical relationship among the supply chain management and business repute in the service sector of Indonesia. To the best of our research, this research is a first in nature which is exploring the relationship between supply chain management and business repute in Indonesian economy. The overall study is quantitative in nature which has collected the data through a survey questionnaire from a sample of 183 respondents in service firms. Descriptive results are showing the moderate trends in the mean score with the relative deviation in the average responses too. Additionally, demographic factors like age, working experience, education, marital status, and working status are also presented through relative frequencies and percentage score. For examining the impact of various factors of supply chain management on business repute, regression analyses have been performed where F-test is showing the fitness of the model. It is found that there is a significant and positive impact of first items of autonomy, first item of environmental mastery, first item of personal relationship, and first and third items of self-acceptance. Whereas the rest of the items are indicating no significant impact on mean business repute in Indonesian service industry. However, study is limited in terms of sample size, missing the impact of behavioral intention on business repute, and implication of both measurement and structural equation modelling approaches. Future studies are recommended to consider these limitations as their fundamental contribution in the literature work.